Cleaner production solution selection for paper making – a case study of Latif paper products Co. Iran. Issue 5 (3rd September 2018) - Azizi, Majid; Asadizadeh, Yaghoob; Ray, Charles; Hamzeh, Yahya
Abstract: The objective of this research is to design an approach for selecting appropriate solutions to efficiently and productively reduce environmental pollution and water, energy and raw material consumption in a recycled paper manufacturing facility, the paper mill in Latif, Iran. To reach this goal, we develop a decision-making model using the Analytic Hierarchy Process (AHP). The proposed model provides a framework for cleaner production implementation specific to the paper industry. Pairwise comparisons of the results of designed questionnaires resulted in the hierarchy model being divided into five major groups: production modification; process change; preventive maintenance; renewal; and manpower resources.These five groups include 31 sub-criteria and seven alternatives. The results showed that process change yields the highest priority among the main criteria and that industrial automation and its technology level gives the highest priority among sub-criteria. Regarding the alternatives, reduction of environmental pollution is the most important solution for cleaner production in the industry. Also, product modification is the most sensitive criterion affecting the alternatives priority.